Case study for oxalate and its related mineral contents in selected fodder plants in subtropical and tropical regions - Abdullah, Ramli; Kawamura, O.; Rahman, M.M.; Ikeue, M.; Niimi, M.; Fukuyama, K.; Wan Khadijah, W.E. (2013)
A survey of oxalate and its related mineral contents in selected fodder plants was conducted in two regions of subtropical Okinawa, Japan and of tropical Savar and Shahzadpur, Bangladesh. A total of 31 samples were taken from 13 fodder species in Okinawa, Southern part of Japan and of 63 samples from 27 fodder species in Bangladesh. The data of both regions revealed that the majority of fodder plants accumulated lower contents of oxalate than the critical level for toxicity at more than 20 g kg-1 DM, while few fodder species (Pennisetum purpureum and Brachiaria mutica) in Bangladesh and only Setaria sphacelatain southern part of Japan reached this critical level. In most of the cases, no relationship was found between oxalate and mineral contents in the plants tested. The results from the present study demonstrate that the oxalate content in tropical fodder species may vary in a wide range, mainly depending on plant species. To be noted is that some fodder species could accumulate oxalate at so high content as might be toxic to ruminants in certain conditions. © 2013 Academic Journals Inc.